Aerogéis de nanocelulose funcionalizados para absorção seletiva de solventes orgânicos - Pereira, André Luís Sousa (2019)
Aerogel is a solid material that presents high porosity, low density and large surface area, with characteristics appropriate for new high value applications. As a consequence, studies are focused on new sources of raw material, processes and treatments aiming at reducing the high cost involved in obtaining them. In this context, plant fibers, especially cellulose, are the most abundant natural polymer and one of the main constituents of plant cell walls, also synthesized by some microorganisms. To expand the range of applications, some studies have investigated the functionalization of aerogels, being an area with high potential to be explored. In the present work, with the objective of establishing a methodology for obtaining aerogels, bacterial cellulose was oxidized by TEMPO, nanofibrillated in blender and silanized with methyltrimethoxysilane. Oxidation and silanization were evidenced by FTIR. Aerogels were produced from this functionalized suspension (CBOXNS) and compared to other non-oxidized (CBN and CBNS) and non-silanized aerogels (CBOXN). All aerogels are very light (density 0.010 to 0.014 g.cm-3) and very porous (porosity 99.8 to 99.4%). The aerogels presented in their morphology a structure organized in lamella formed of webs of microfibrils. The aerogels of CBOXNS presented a lower absorption capacity of organic oils and solvents (35 to 75 times the own weight) than those of CBN and CBNS, but higher mechanical properties (tension of 13.0 kPa and elasticity modulus of 39.4 kPa ), which allowed its use for 7 absorption-drying cycles, maintaining an absorption capacity of 83%. The CBOXNS aerogel presented the best balance among all tested properties and was used as a model for cashew juice permeate bacterial cellulose (CBP) and eucalyptus cellulose (CE). The aerogels of oxidized and silanized CBP (CBPOXNS) and oxidized and silanized CE (CEOXNS) are also very light (~ 0.011 g.cm-3) and very porous (~ 99.4%), have lower mechanical properties (3,1 kPa and modulus of elasticity of 10,7 and 3,1 kPa) when compared to the aerogels of CBOXNS, but they have a high capacity of absorption of oils and organic solvents, being the aerogel of CBPOXNS a great absorber of oils (65 times the own weight) and CEOXNS aerogel a great organic solvent absorber (55 to 80 times its own weight).